Analisis Perbedaan Nilai Hematokrit pada Penderita Hipertensi Derajat Satu dan Derajat Dua - Djami, Supriati Wila; Tangkelagi, Marni; Bria, Meliance; Loaloka, Meirina Sulastri (Jaringan Laboratorium Medis, 2024)
Blood pressure is the pressure exerted by blood against the walls of blood vessels and is generated by the pressure of blood against the walls of arteries when the blood is pumped from the heart to the tissues. The amount of pressure varies depending on the blood vessels and heart rate. Hypertension is a non-communicable disease that triggers health problems that occur throughout the world. Kupang Regency is one of the districts with the highest cases of hypertension in NTT province with 1,582 cases. Hypertension is closely related to hemoglobin levels, hematocrit values and erythrocyte counts. There is a significant positive relationship between hematocrit values and diastolic blood pressure. Increased blood pressure has a significant positive relationship between hemoglobin levels, hematocrit values and erythrocyte counts. Apart from that, factors that influence hypertension with hemoglobin levels, hematocrit values and erythrocyte counts are age, gender, circulating fibrinogen and red blood cell aggregation. The aim of this research is to determine the difference in hematocrit values in sufferers of grade one and degree two hypertension. This research uses a cross-sectional analytical research design based on primary data originating from examination results in Bone Village, Nekamese District, Kupang Regency in April 2023 which meets the research sample criteria. Sampling for this research was determined using the Purposive Sampling technique. The research respondents were 30 hypertension sufferers in Bone Village, Nekamese District, Kupang Regency. Research on blood pressure and hematocrit values was carried out on all respondents. The results showed that hypertension sufferers consisted of 5 (17%) men and 25 (83%) women with the highest age of hypertension sufferers being 56 years old, 24 people (80%). There were 9 (30%) people suffering from grade 1 hypertension and 21 (70%) people suffering from degree 2 hypertension with the hematocrit value of most hypertensive sufferers still within normal limits, 18 (60%) and low hematocrit values as many as 12 (40%). The results of this study were processed using SPSS software with Mann-Whitney Test analysis and presented descriptively regarding the analysis of hematocrit values in sufferers of degree one and degree two hypertension. The results of statistical analysis show p-value 0.05, which means there is no significant difference between variables and vice versa. The results of the study showed that there was no difference in hematocrit values in sufferers of degree one and degree two hypertension with a value of p=0.295. In this study, hypertension sufferers generally had normal hematocrit values, but in second-degree hypertension sufferers the hematocrit values tended to be low.